Life‐saving case of cardiopulmonary arrest by secondary aortoenteric fistula formed in the anastomotic site between the inferior mesenteric artery and aortic graft. Issue 1 (25th March 2022) - Yagi, Masayuki; Aiboshi, Junichi; Kojima, Mitsuaki; Yoshikawa, Shunsuke; Morishita, Koji; Kaji, Masahito; Otomo, Yasuhiro
Abstract : Background: Secondary aortoenteric fistula is a fatal cause of gastrointestinal bleeding after aortic reconstructive surgery with a prosthesis. In most cases, the proximal suture line is involved. We herein report a rare case in which the fistula formed between the suture line of inferior mesenteric artery reimplantation and the jejunum. Case Presentation: An 82‐year‐old man was transferred to our hospital due to hematemesis with severe hypovolemic shock. Although he fell into cardiopulmonary arrest, immediate resuscitation achieved return of spontaneous circulation. As his surgical history of aortic reconstruction and computed tomography findings suggested potential secondary aortoenteric fistula, emergency surgery was carried out. The anastomosis between the inferior mesenteric artery and aortic graft was communicating with the jejunum. Partial jejunal resection was undertaken, and the aortic graft was replaced. Conclusion: The anastomosis between the inferior mesenteric artery and aortic graft in the previous aortic replacement can become the site of secondary aortoenteric fistula. Abstract : A rare case of secondary aorto‐enteric fistula (SAFE), in which the fistula existed between a suture line of IMA reimplantation and jejunum. For treatments of SAFE, accurate and immediate diagnosis and surgery are required.